Critical Thinking and Cognitive Engagement in Social Sciences: A Collaborative Experiential Model within a Seamless Learning Ecosystem - Bety D.S. Hetharion (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students' low thinking ability impacts their interpretation, analysis, and integration of new information. The 2018 international student assessment program indicates Indonesian students are at a minimum literacy level, ranking at PISA level 2. This study employs a combination of the Collaborative Experiential Model and the Seamless Learning Ecosystem model to enhance learning effectiveness and efficiency, leveraging technology to improve student abilities. An experimental method was used, incorporating face-to-face and online learning modalities. The analysis revealed significant validity (p ≤ 0.05) across 24 question items, with Cronbach's alpha values of 0.781 and 0.762, indicating high reliability. Both pre-test and post-test activities utilized these valid and reliable questions. Homogeneity tests showed significance values of 0.869 and 0.757 for cognitive participation and critical thinking variables, respectively. Consequently, the seamless learning ecosystem model demonstrably enhances critical thinking skills and learning outcomes.